Implementasi Program Edukasi Keselamatan Kebakaran Dalam Upaya Pencegahan dan Pengendalian Kebakaran di RS X Kota Dumai - Annisa Wahdania; Santoso Santoso; Lita Lita; Herniwanti Herniwanti; Makomulamin Makomulamin; Asril Asril (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Fire incidents in hospitals pose a serious safety threat that requires systematic prevention and control measures. This study aimed to identify factors influencing fire prevention and control in a hospital in Dumai City using a quantitative approach with a cross-sectional design, involving hospital staff selected through simple random sampling. Data were collected using a structured questionnaire that had been tested for validity and reliability, and were analyzed using association tests and multivariable analysis to examine the influence of variables. The findings indicated that most respondents demonstrated good levels of fire prevention and control practices, and there were significant associations between attitude, emergency response simulation, and supervision with fire prevention and control efforts. Attitude emerged as the most dominant factor, indicating that respondents with negative attitudes were more likely to have poor fire prevention and control practices compared to those with positive attitudes, with this relationship controlled by knowledge. It can be concluded that work capacity influencing fire prevention and control includes attitude as the primary factor, supported by knowledge, emergency response simulation, and supervision. Therefore, it is recommended that the Hospital Occupational Health and Safety Committee strengthen positive attitudes among staff, enhance the quality of emergency response simulations, and implement consistent supervision to support effective fire prevention and control.